NIP-tomografia usando método CRS e dados sísmicos marinhos - AFONSO, João Batista Rodrigues (Universidade Federal do Pará, 2019)
This work consisted on the application of techniques for processing, inversion and imaging of the Marmousoft synthetic data, and of the Jequitinhonha real data obtained on the eastern Atlantic continental shelf of the State of Bahia. The convencional NMO and CRS stack methods, and NIP-tomographic inversion were applied to the mentioned data. The NMO stack served to produce RMS and interval velocity distribution maps on the semblance domain. The CRS stack of both data we used for picking of re ection events to obtain the wave eld parameters that served to constrain the model as input for the NIP-tomographic inversion. The inversion characterizes as resulting in a smooth velocity model. Kirchhoff depth migration was used for verifying the obtained velocity models. We critically analyzed the applied techniques, and compared the CRS and the NMO stacks. The evolution of the visual quality of the obtained CRS and NMO sections were analyzed as measured by event continuity trace-by-trace and the signal/noise ratio. The di erences and improvements on the velocity model obtained by NIP-tomographic were also analyzed. The Kirchhoff prestack depth migration was applied aiming at geological interpretations, and to point out for better conditions of processing and imaging.